2nd EUt+ Conference on Merging New Trends and Consolidating Good Practices in Languages for Specific Purposes (EUtLC2025 - (:unkn) unknown (My University, 2026)
2nd EUt+ Conference on Merging New Trends and Consolidating Good Practices in Languages for Specific Purposes (EUtLC2025), Universidad Politécnica de Cartagena, Cartagena, Spain, June 2025. (Contributed to the editorial and peer-review process for conference proceedings)